Characterisation of surfaces modified through self-assembled monolayers and click chemistry - Coates, Megan Patricia (Rhodes University, Faculty of Science, Department of Chemistry, 2013)
Different approaches to surface modification were investigated in this work on gold, glassy carbon, multi-walled carbon nanotube paper and on single-walled carbon nanotubes adsorbed on glassy carbon. These approaches include electrochemical grafting, electropolymerisation, click chemistry, axial ligation, adsorption and self-assembled monolayers. The modified surfaces were characterised using a variety of techniques; predominantly electrochemistry, scanning electrochemical microscopy and X-ray photoelectron spectroscopy. For the formation of self-assembled monolayers on gold, four new manganese(III) phthalocyanines (1a-d), octa-substituted at the peripheral position with pentylthio, decylthio, benzylthio, and phenylthio groups were synthesized and characterised. X-ray photoelectron spectroscopy was used to show the formation of a sulphur-gold bond. A number of approaches using 4-azidoaniline (2a) combined with azide-alkyne click chemistry and electrochemistry were also used to anchor ferrocene and pyridine moieties on to the carbon surfaces, including direct in situ diazotation and grafting, electropolymerisation, and the synthesis of the diazonium salt followed by grafting. Iron phthalocyanine was linked to the pyridine-clicked surfaces through axial ligation, where the strong axial bond formed by the interaction between the central metal and the lone pair of the nitrogen in the pyridine group resulted in stable modified electrodes. The potential of these surfaces for the detection of analytes such as thiocyanate, hydrazine and sulphite are briefly shown as well. This work also describes for the first time the possibility of performing local micro-electrochemical grafting of a gold substrate by 4-azidobenzenediazonium (2b) using scanning electrochemical microscopy in a single and simple one step approach, without complications from adsorption.
Keywords: Monomolecular films; Gold; Adsorption; Nanotubes; Self-assembly (Chemistry); Scanning electrochemical microscopy; X-ray photoelectron spectroscopy